A study on double fillet lap welding of thin sheet AZ31B magnesium alloy by low power fiber laser - Muhammad Naqiuddin, Mat Salleh (2017)
This thesis presents a study on laser welding of thin sheet AZ31B Magnesium (Mg) alloys using low power fiber laser. AZ31B is known as the lighter metal compared to aluminium alloys and steel with the density of 1.78 g/cm3. Thin sheet AZ31B finds its application in automotive, aviation and also electronic devices parts such as computer casing and thin plate part in smartphone. In joining thin sheet AZ31B, laser welding is promising the best joining method compared to arc and solid state welding in producing small weldments. A low power fiber laser welding has been chosen in this research work and the welding parameters are optimized by response surface method (RSM) using Box-Behnken design (BBD) method in order to provide the most suitable laser welding condition to weld this thin AZ31B. Welding as thin as 0.6 mm of AZ31B, laser welding by double fillet lap joint configuration is selected as it can produce lower heat input with high power due to the weld geometry of fillet lap joint which beam focused at the edge of upper sheet. It was preferred since the usage of laser was overwhelming especially in manufacturing industries. The first objective ofthis work is to optimize the laser welding parameters to weld double fillet lap joint on AZ31B. The second objective is to investigate the relation of microstructure changes on mechanical properties of this joint. According to design of experiment (DOE) generated by BBD, 15 samples are welded and their strength were tested using tensile-shear test. From the response, a mathematical model is constructed after the analysis of variance (ANOV A) has been performed. To discuss the relationship between the shear strength and microstructure, welded samples are cut at the stable weld's cross section and are prepared for the macro and microstructure observation. Sample 9 possesses the highest shear strength with 62.0 MPa and fracture load of 740 N. A mathematical model with quadratic equation was produced to calculate the tensile shear strength. For validation of mathematical model, percentage errors for all samples are less than 8 %. It shows a high accuracy of the model and it was accepted. Welding parameters then proceed to be optimized. The optimized parameters were; pulsed energy (EP): 2.2 J; welding speed (WS): 2.0 mm/s; and angle of irradiation (AOI): 2.0 °. The percentage error for the optimized sample was 0.79 %. Vickers hardness test was performed at the weld area for sample with highest and optimized parameter sample in order to compare the result. It was observed that most of the welded samples have the solidification crack at the weld centre area of the second weld and this defect contributed to the lower tensile shear strength as observed from macrograph. For microstructure, finer grain produced at the fusion zone (FZ) of upper sheet compared to the FZ near the transition line which produced coarser and medium grain. Optimized sample was fractured at the transition region of upper sheet, meanwhile sample 1 fractured at the weld due to the crack defect. It was observed that the fracture was brittle. The fine grain produced higher hardness values compared to the coarser grain with a value of 77 Hv for the optimized sample. Optimized sample has 80.5 MPa of tensile shear strength and fracture load of 800 N which could be applied in replacing AI and steel especially for the electronic parts since the strength was acceptable for a thin product.